The effect of calcination on the microwave dielectric properties of Ba(Mg1/3Ta2/3)O-3 - Fang, YH; Hu, A; Ouyang, SX; Oh, Young Jei (ELSEVIER SCI LTD, 2001)
In this study, the role of calcination, its effect upon microstructural development and the correlation with dielectric losses at microwave frequencies were investigated. Ceramics with the composition Ba(Mg1.3Ta2/3)O-3 (BMT) were prepared by a conventional mixed-oxide route using controlled calcination. Commercial processing often uses sintering and calcination conditions to modify the dielectric properties of ceramics. However, the mechanism by which the calcination conditions influence the dielectric losses is not clear. The BMT powders were calcinated at 1000-1300 degreesC for 4-10 h in air or flowing oxygen. Resonator samples were then sintered at 1600-1650 degreesC for 3 It. Scanning electron microscopy and X-ray diffraction were used to examine the phase composition and the microstructure of the sintered bodies. The microwave dielectric properties were measured at 10 GHz. We found a significant influence of the calcination conditions on the quality factor (Qf) -value. The influences of the phase composition on dielectric losses appear to dominate those of the microstructure. A significant effect was also found for specimens calcinated in different atmospheres. By controlling the calcination and sintering a pure BMT ceramic with a dielectric constant of 24.5, a Qf -value of 120,000 GHz and an r tau (f) of 6 ppm/degreesC was obtained. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: CERAMICS